Effect of different nitrogen fertilizer application rates on Dichrostachys cinerea and Acacia karroo sapling growth, foliar nutrient and antinutrient concentrations in a southern African savanna - Nyamukanza, Casper C.; Sebata, Allan (John Wiley and Sons Inc., 2021)
Nitrogen (N) fertilization influences woody plant growth, foliar nutrient and antinutrient concentrations. We conducted a nursery experiment to determine the effect of five N fertilization rates on Dichrostachys cinerea and Acacia karroo sapling height, basal diameter, growth of longest shoots and root length, crude protein (CP), acid and neutral detergent fiber (NDF), condensed tannins (CT) and total phenolic (TP) concentrations. Eight potted plants of each woody species were allocated to each of five N fertilization rates (0, 0.21, 0.42, 0.63 and 0.84 g N/kg of soil) in a completely randomized design. Different N fertilization rates did not result in varying plant growth in terms of height, stem diameter and root length in both D. cinerea and A. karroo. However, N fertilization rate of 0.63 g N per kg of soil resulted in an increase in length of the longest shoot in both D. cinerea and A. karroo. Foliar CP increased with an increase in N fertilization rate up to 0.63 g N per kg of soil, while acid and NDF, CT and TP were lowest at N fertilization rates of 0.63 g N per kg of soil in both D. cinerea and A. karroo. We conclude that N did not limit plant growth, and therefore N fertilization is unlikely to significantly improve sapling growth. However, N fertilization improved foliar CP and reduced CT and TP concentrations in both D. cinerea and A. karroo improving their nutritive value to browsers.